(untitled) (Journal of Dhaka Medical College, 2010)
Purpo’e: To evaluate functional & anatomical results of the Colles’ fracture treated by two methods- i) Closed reduction & precutaneous kirschner wire (K- wire) fixation combined with plaster cast & ii) Conventional plaster cast immobilization after closed reduction. Methods: A randomized prospective comparative study was done from July 2003 to June 2005 on 52 patient with Colles’ fracture in NITOR, Dhaka. 12 patients lost from follow up. Twenty patient (20) in each group were finally available for evaluation. The group treated by closed reduction & percutaneous K-wire fixation combined with plaster cast- designated as "Arm A" & another group treated conventionally by plaster cast only designated by "Arm-B". Male Female ratio was 1:3, Age range was 35 to 70 years (Mean age 52.5 years) Distribution of limbs side involvement almost equal. Mode of injuries were domestic fall & RTA (4:1) According to AO classification fracture were in both groups- A2 = 13, A3 = 10, C1 = 6, C2 = 8 & C3 = 3 (Total- 40). Follow up period was 6-14 months (mean = 6 month) Results: Union time for most of the fractures was 6-8 weeks. At final follow up Satisfactory Anatomical end results of percutuneous fixation group (Arm-A) were 80% and in conventional plaster cast group (Arm-B) were 35%. (P<0.01). Satisfactory functional end results in Arm-A group were 70% and in Arm-B group were 30% (P<0.01) Complications seen much more in conventional group (Arm-B) than percutaneous K-wire fixation group (Arm-B). Sarmiento & Latta’s criteria was used to evaluate the progress. Conclusion: The coventional plaster cast method for treatment of colles’ fracture usually can’t maintain radial length & angulation in many instances and results significant anatomical difficultly and functional disability. On the other hand after close reduction additional fixation in the form of percutaneous crossed K-wire can maintain the reduction till bony union & prevent late collapse at fracture site & provides better result. Key Words: Colles’ fracture; closed reduction; Plaster cast & Kirschner wire (K-wire) fixation DOI: 10.3329/jdmc.v17i2.6591 J Dhaka Med Coll. 2008; 17(2) : 98-105